2005
DOI: 10.1063/1.1977187
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanopencils: Efficient field emitters

Abstract: ZnO nanopencils were synthesized on a silicon wafer without catalysts at a low temperature of 550 ° C through a simple two-step pressure controlled thermal evaporation. Penholders were well-hexagonal faceted and the diameter of pen tips on the nanopencils was in the range of 20–30 nm. High-resolution transmission electron microscopy shows that the nanopencils were single crystals growing along the [0001] direction and the pen tips subtend a small angle with multiple surface perturbations. Field-emission measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
115
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(123 citation statements)
references
References 17 publications
4
115
0
Order By: Relevance
“…For SiC film deposited with 120W DC power, the turn-on field (defined as the E where the J can be distinguished from the background noise) was measured to be 4.5V/ m, the threshold field (defined as the E where the J is as high as 0.05mA/cm 2 ) was measured to be about 6.8V/ m and the field emission current density reached to 0.48mA/cm 2 at applied electric field of 10V/ m, which indicates that SiC thick film has high ratio of electron emission property. They are comparable to those values measured from other field emission materials, such as ZnO [8], etc. The field emission property of the SiC thick films was also investigated by the classical Fowler-Nordheim theory, which can be described as follows: , φ is the work function of the emission tip (eV), the factor describes the geometrical efficiency and equals to the percentage of the actual emitting surface area to the total surface area.…”
Section: Resultssupporting
confidence: 77%
“…For SiC film deposited with 120W DC power, the turn-on field (defined as the E where the J can be distinguished from the background noise) was measured to be 4.5V/ m, the threshold field (defined as the E where the J is as high as 0.05mA/cm 2 ) was measured to be about 6.8V/ m and the field emission current density reached to 0.48mA/cm 2 at applied electric field of 10V/ m, which indicates that SiC thick film has high ratio of electron emission property. They are comparable to those values measured from other field emission materials, such as ZnO [8], etc. The field emission property of the SiC thick films was also investigated by the classical Fowler-Nordheim theory, which can be described as follows: , φ is the work function of the emission tip (eV), the factor describes the geometrical efficiency and equals to the percentage of the actual emitting surface area to the total surface area.…”
Section: Resultssupporting
confidence: 77%
“…Similar results were also observed on NW samples with rough surfaces. 17,[23][24][25] In the growth process of GaN NWs with nanoscale protrusions, it is expected that the Ga vapor reacts with the N vapor, which is decomposed from the NH 3 at a high temperature of 950°C to form the GaN structure. It has been reported that hydrogen has a higher surface mobility and can stream easier and faster than the products of GaN molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Such growth of nanowires on nanorods clearly shows that the two-stage process governed by the growth disparity along different facets indeed leads to preferential growth along the ½000 " 1 plane. 49 After a critical thickness is reached, the nanorods become nanowires, probably due to loss of substrate influence. This quasi-one-dimensional structure, as shown in the form of needles in Fig.…”
Section: Resultsmentioning
confidence: 99%